Taxonomic revision of Israeli snakes belonging to the Platyceps rhodorachis species complex (Reptilia: Squamata: Colubridae) - Sinaiko, Guy; Magory-Cohen, Tali; Meiri, Shai; Dor, Roi (Zootaxa, 2018)
The Platyceps rhodorachis species complex encompasses a widespread group of morphologically similar colubrid snakes. The number and identities of species from this complex in Israel have recently been debated. Studies from the previous decade concluded that there are two species in Israel and its vicinity (compared with one previously recognized), but their identity remained contested. We estimated the number of species and their taxonomic identity using morphological and molecular data. We found some evidence for clinal variation in many of the characters used to differentiate the species, and a great overlap in traits of putative species. Genetic data revealed very low sequence divergence, with all putative species being paraphyletic. Platyceps rogersi emerged as genetically closer to Platyceps saharicus rather than to its putative conspecific, P. karelini. The phylogenetic and taxonomic results thus indicate that the Israeli populations of the P. rhodorachis complex all belong to a single species, Platyceps saharicus (Schätti & McCarthy 2004).